Pengaruh Pengalaman Auditor dan Motivasi Auditor Terhadap Kualitas Audit Dengan Efektifitas Program Audit Sebagai Pemoderasi - Rianto -; Diniyanti - (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
This study aims to determine empirically the work experience, motivation and effectiveness of the audit program on audit quality through the effectiveness of the audit program as a moderating variable. The formulation of the problem of this research is to find out whether work experience, auditor motivation and effectiveness of the audit program affect the quality of audit. This research was conducted at Public Accounting Firm in Bekasi Region. Sampling technique used is purposive sampling with quantitative research type. Data analysis method used is SEM model (Structural Equation Model) with PLS analysis tool. The results of this study indicate that the work experience has a significant effect on audit quality. The auditor's motivation has a significant effect on the quality of audit. The effectiveness of the audit program has no significant effect on the quality of the audit. Effectiveness does not successfully moderate the work experience on audit quality. Effectivity successfully moderates the motivation on audit quality.Suggestions related to the results of this study is that in order for auditors to produce optimum audit quality it is necessary to increase the motivation and implementation of audit programs effectively, it may be facilitated by the public accounting firm in Bekasi. The scope of this research is only conducted in the Public Accounting Firm in Bekasi area so to get general conclusions need to do a wider research